2001
DOI: 10.1093/humrep/16.9.1959
|View full text |Cite
|
Sign up to set email alerts
|

Laser zona pellucida thinning—an alternative approach to assisted hatching

Abstract: These results suggest that laser zona thinning is effective and may provide significant advantages over conventional assisted hatching techniques, which create holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 29 publications
4
50
2
1
Order By: Relevance
“…More recently, Blake et al [56] demonstrated a significant increase in hatching in vitro, using the laser to thin the zona pellucida without creating a hole. A further study found a higher clinical pregnancy rate when using the laser to thin an extended area of the zona pellucida compared with producing a single full thickness hole [57].…”
Section: Laser-assisted Hatchingmentioning
confidence: 99%
“…More recently, Blake et al [56] demonstrated a significant increase in hatching in vitro, using the laser to thin the zona pellucida without creating a hole. A further study found a higher clinical pregnancy rate when using the laser to thin an extended area of the zona pellucida compared with producing a single full thickness hole [57].…”
Section: Laser-assisted Hatchingmentioning
confidence: 99%
“…LAH can improve the clinical pregnancy rate of the thawing cycle. Since LAH can be divided into artificial thinning of the zona and drilling of the zona, previous findings have shown that the former is better than that the latter in vitro (15,16). Hiraoka et al have shown that vitrification can increase the hardness of zona, and the embryo implantation and clinical pregnancy rates in the half ZP thinning FET cycle was superior to that of a quarter ZP, although these studies lacked a control group (1).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ZP dissection with glass pipettes [7] or chemical ZP opening using acidic Tyrode's solution [8,9] are in wide use. Recently, AH by 1.48 μm diode laser has been introduced and has enabled to reliably produce equally sized ZP opening [10][11][12][13]. However, studies evaluating the effect of the size of ZP opening by laser AH for frozen cleaved embryos are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies evaluating the effect of the size of ZP opening by laser AH for frozen cleaved embryos are lacking. One reason for this may be due to the fear that opening the ZP at the cleavage stage may have adverse effect such as loss of blastomeres through the opened ZP [11,12]. This problem can be overcome by performing AH at the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%